OPTIMAL TREATMENT STRATEGY FOR PATIENTS WITH PROGRESSIVE SQUAMOUS CELL CARCINOMA OF THE HEAD AND NECK - L. V. Bolotina; C. A. Kravtsov; T. V. Ustinova; E. Yu. Karpenko; A. L. Kornietskaya; A. A. Paichadze; V. N. Galkin; A. D. Kaprin; A. A. Fedenko (Исследования и практика в медицине)
The treatment of common forms of squamous cell carcinoma of the organs located on the head and neck that are not subject to surgical treatment is limited to the use of chemoradiotherapy with platinum derivatives or drug therapy with platinum-containing regimens. With the progression of the disease, ineffective 2‑line cytostatics were prescribed that did not fundamentally change the course of the tumor process. The introduction into clinical practice of drugs of the original mechanism of action has significantly increased the effectiveness of drug therapy during progression after platinum-containing chemotherapy. The article presents two clinical observations that demonstrate the relevance of the strategy of using inhibitors of immune response control points after platinum preparations.